Validation of the Fung double tube to enumerate Clostridium perfringens from the intestinal contents of broiler chickens raised on different diets - Barrios Godoy, Miguel Alejandro (Kansas State University, 2012)
Clostridium perfringens causes necrotic enteritis (NE), resulting in decreased feed efficiency and increased mortality, costing the poultry industry USD 2 billion a year worldwide. The objective of the first trial was to validate the Fung Double Tube (FDT) to detect and enumerate C. perfringens in chicken intestines. Two methods (FDT and petri plates) and three media (Shahidi Ferguson Perfringens [SFP] with egg supplement, polymyxin B [p], and kanamycin [k; E]; SFP with p and k [P]; and SFP with cycloserine [C]) were arranged in a 2 x 3 factorial, resulting in six treatments. The FDT with medium C (5.35 log CFU/g) had significantly (P<0.05) higher C. perfringens counts than any other media/method combination. The objective of the second and third trials was to determine the effect of diet type on the population of C. perfringens in broiler intestines using the FDT. Trial 2 tested: corn-soybean meal (SBM), low-crude protein (19.8%)/high synthetic amino acids (SAA), and barley (56%)-fishmeal (4%; BF). Diets in Trial 3 included: corn-SBM, barley (7.46%), fishmeal (4%), and BF. Diets in Trial 2 contained an antibiotic and a coccidiostat; diets in Trial 3 did not. After 21 days, birds in Trial 2 fed BF had significantly higher (P<0.05) counts (5.96 log CFU/g) of C. perfringens, as compared to all other diets. Both, corn-SBM and SAA diets resulted in 3.89 log CFU/g. In Trial 3, birds fed the corn-SBM diet (2.7 log CFU/g) had significantly lower (P<0.05) counts than broilers fed BF (4.15 log CFU/g). When broilers were fed fishmeal (3.583 log CFU/g) and barley (3.577 log CFU/g) separately, C. perfringens counts were numerically higher compared to the corn-SBM diet, but numerically lower than birds fed BF. Barley and fishmeal inclusion increased the incidence of C. perfringens, and their combination resulted in a cumulative effect. The FDT method is able to detect C. perfringens at higher levels than the conventional petri plate method (P<0.001) and it also proved to be an effective method to detect differences in C. perfringens counts from the intestines of chickens fed different diet.
Keywords: Fung double tube; Clostridium perfringens; Broilers; Barley; Fishmeal; Anaerobic method; Animal Diseases (0476); Animal Sciences (0475); Veterinary Medicine (0778)